2010
DOI: 10.2174/156720510790274491
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimers Disease and Retinal Neurodegeneration

Abstract: Alzheimer's disease (AD) is the major cause of dementia in the world. Although the entorhinal cortex and hippocampal complex are best known as the sites of early pathology in AD, increasing evidence shows that the eye, particularly the retina, is also affected. The AD-related changes in the retina are associated with degeneration and loss of neurons, reduction of the retinal nerve fibres, increase in optic disc cupping, retinal vascular tortusity and thinning, and visual functional impairment. Given the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 150 publications
(243 reference statements)
2
73
0
Order By: Relevance
“…A side effect of this research, however, has been the finding that A β deposition occurs in the lenses of AD subjects [61] and has been found in lenses and corneas of single and double transgenic animal models [111]. A β deposition and hyperphosphorylated tau have also been detected in the lenses and corneas of triple transgenic mice [81] raising the slightly unexpected but equally welcome possibility that an ocular biomarker for AD may exist that is not connected with the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…A side effect of this research, however, has been the finding that A β deposition occurs in the lenses of AD subjects [61] and has been found in lenses and corneas of single and double transgenic animal models [111]. A β deposition and hyperphosphorylated tau have also been detected in the lenses and corneas of triple transgenic mice [81] raising the slightly unexpected but equally welcome possibility that an ocular biomarker for AD may exist that is not connected with the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Both NTG and POAG are prevalent in senile populations 61,93. Some studies showed evidence that the anti-Alzheimer agents exhibit benefit to POAG patients 106,107. Thus, presently, more and more researchers consider glaucomas as a group of aging-related disease similar to neurodegenerative disease in the central nervous system 108,109…”
Section: The Current Concepts Regarding the Relationship Between Ntg mentioning
confidence: 99%
“…Since then, the reports of retinal pathology in patients with AD have grown to include RGC loss, NFL atrophy, thinning of the macular ganglion cell complex, and widespread axonal degeneration in the optic nerve [17, 19, 21, 22, 38, 73, 81, 92, 97, 147, 174]. Other changes, such as blood flow rate [19, 50, 59, 183], signs of inflammation [20, 21], and varied cellular degeneration mirroring those observed in the AD brain may reflect cerebral pathology [21, 76, 128, 186], but do not indicate AD as strongly as disease hallmarks.…”
Section: Introductionmentioning
confidence: 99%